Improving machine virtualization with 'hotplug memory' - Pinter, S. S.; Aridor, Y.; Shultz, S.; Guenender, S. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2005: Anais do XVII International Symposium on Computer Architecture and High Performance Computing, 2005)
Machine virtualization has emerged as a key technology for server consolidation and on-demand server provisioning. To support this trend, it is essential to improve the performance of virtualization software and hence enable the efficient running of many virtual machines. We present a virtualization system that can dynamically extend the real memory of its guest virtual machines. We describe an implementation of dynamic memory extension for Linux guests running on the IBM zVM virtualization environment. Our implementation for the Linux extension is based on device drivers for accessing these dynamic memory extensions. Moreover, we show that this new capability can improve utilization and performance of the Linux guests in our virtualization environment. Specifically, memory management is improved and more virtual machines can run at a given moment. We study the utilization of dynamic memory extension of a Linux guest for a JVM heap. Running Specjbb2000 benchmark on a small virtual machine extended with dynamic memory to host the heap, we measured an improvement in transaction throughput and a 23.23% reduction in paging activity compared to an initially large machine. We further studied the implication of our experiments on the number of virtual machines that can run efficiently.